2004
DOI: 10.1111/j.1538-7933.2004.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial segregation of venous thromboembolism

Abstract: Summary. Background: Venous thromboembolism (VTE) is postulated as a complex disease, but the heritability and mode of inheritance are uncertain. Objective: To determine if VTE (i) segregates in families; (ii) is attributable to inheritance, shared environment, or both; and (iii) the possible mode of inheritance. Patients and methods: In a family-based study of relatives from 751 probands (60% female) with objectively diagnosed VTE (without cancer), we performed complex segregation analyses corrected for mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 33 publications
1
98
0
1
Order By: Relevance
“…41,42 Inherited reductions in plasma natural anticoagulants (eg, antithrombin, protein C, or protein S) have long been recognized as uncommon but potent risk factors for venous thromboembolism. 43 More recent discoveries of impaired downregulation of the procoagulant system (eg, activated protein C [APC] resistance, Factor V Leiden), increased plasma concentrations of procoagulant factors (eg, factors I [fibrinogen], II [prothrombin], VIII, IX, and XI) and increased basal procoagulant activity, impaired fibrinolysis, and increased basal innate immunity activity and reactivity have added new paradigms to the list of inherited or acquired disorders predisposing to thrombosis (thrombophilia).…”
Section: The Genetic Epidemiology Of Venous Thromboembolismmentioning
confidence: 99%
“…41,42 Inherited reductions in plasma natural anticoagulants (eg, antithrombin, protein C, or protein S) have long been recognized as uncommon but potent risk factors for venous thromboembolism. 43 More recent discoveries of impaired downregulation of the procoagulant system (eg, activated protein C [APC] resistance, Factor V Leiden), increased plasma concentrations of procoagulant factors (eg, factors I [fibrinogen], II [prothrombin], VIII, IX, and XI) and increased basal procoagulant activity, impaired fibrinolysis, and increased basal innate immunity activity and reactivity have added new paradigms to the list of inherited or acquired disorders predisposing to thrombosis (thrombophilia).…”
Section: The Genetic Epidemiology Of Venous Thromboembolismmentioning
confidence: 99%
“…4,5 Twin and family studies among populations of EA suggest that genetic factors explain up to 60% of VTE heritability. 8,9 Genome-wide association studies (GWASs) in populations of EA have confirmed the 2 well-established risk variants, factor V Leiden (rs6025) and prothrombin G20210A (rs1799963), and have identified several singlenucleotide polymorphisms (SNPs) in the ABO blood group gene (ABO) as susceptibility loci. [10][11][12] However, these variants are found in higher frequencies among individuals of EA compared with AAs, particularly rs6025 and rs1799963 which are nearly absent in AAs.…”
Section: Introductionmentioning
confidence: 99%
“…The heritability of venous thrombosis is high at 50% to 60%. [8][9][10] Previously, we showed that a positive family history of venous thrombosis increases the risk of venous thrombosis even when a genetic risk factor has been identified, suggesting the presence of additional unidentified genetic risk factors. 11 Genome-wide association studies have identified common genetic variants with a modest effect on risk.…”
mentioning
confidence: 97%